The Influence of Demographic and Economic Factors on the Widow’s Reverse Annuity Benefits in Coronavirus Pandemic - Marciniuk Agnieszka; Zmyślona Beata (Wroclaw Review of Law, Administration and Economics)
The COVID-19 pandemic has affected many areas of society and the economy. In the epidemiological field, it has significantly increased mortality, especially in the elderly population. It has greatly affected the real estate and financial market. The price of housing, inflation, and interest rates rose. Therefore, housing is currently unaffordable. The analysis of the Life Expectancy Tables jumped to a higher risk of death for men than for women. The pandemic has made women more likely to be widowed than men, and more often, while their economic and social status has worsened.